Interprofessional education interventions for healthcare professionals to improve patient safety: a scoping review - Yan Jiang; Yan Cai; Xue Zhang; Cong Wang (Medical Education Online)
Background Patient safety incidents, such as adverse events and medical errors, are often caused by ineffective communication and collaboration. Interprofessional education is an effective method for promoting collaborative competencies and has attracted great attention in the context of patient safety. However, the effectiveness of interprofessional education interventions on patient safety remains unclear. This scoping review aimed to synthesize existing studies that focused on improving patient safety through interprofessional education interventions for healthcare professionals.Methods Six databases, including Medline (via PubMed), Embase, Cochrane Library, CINAHL (via EBSCO), Scopus and Web of Science, were last searched on 20 December 2023. The search records were independently screened by two researchers. The Joanna Briggs Institute Critical Appraisal Tool for Quasi-Experimental Studies was used for quality appraisal. The data were extracted by two researchers and cross-checked. Finally, a narrative synthesis was performed. The protocol for this scoping review was not registered.Results Thirteen quasi-experimental studies with moderate methodological quality were included. The results revealed that the characteristics of current interprofessional education interventions were diverse, with a strong interest in simulation-based learning strategies and face-to-face delivery methods. Several studies did not assess the reduction in patient safety incidents involving adverse events or medical errors, relying instead on the improvements in healthcare professionals’ knowledge, attitude or practice related to patient safety issues. Less than half of the studies examined team performance, based primarily on the self-evaluation of healthcare professionals and observer-based evaluation. There is a gap in applying newer tools such as peer evaluation and team-based objective structured clinical evaluation.Conclusion Additional evidence on interprofessional education interventions for improving patient safety is needed by further research, especially randomized controlled trials. Facilitating simulation-based interprofessional education, collecting more objective outcomes of patient safety and selecting suitable tools to evaluate teamwork performance may be the focus of future studies.